Mental health service use and shortages among a cohort of women living with HIV in Canada - Seerat Chawla; Angela Kaida; Marie-Josée Brouillette; Bluma Kleiner; Danièle Dubuc; Lashanda Skerritt; Ann N. Burchell; Danielle Rouleau; Mona Loutfy; Alexandra de Pokomandy; the CHIWOS research team (BMC, 2024)
Abstract Background The prevalence of mental health conditions among women with HIV in Canada ranges between 29.5% and 57.4%, highlighting the need for accessible mental health care. We aimed to (1) describe the availability and use of mental health services among women with HIV and (2) identify characteristics associated with reporting that shortages of these services presented a problem in their care. Methods Baseline data from the Canadian HIV Women's Sexual and Reproductive Health Cohort Study were analysed. Self-reported availability and use of mental health services were examined using descriptive statistics. Participants indicated whether a lack of mental health support was a problem in their care. Logistic regression models were constructed to determine associations between sociodemographic, clinical, and psychosocial characteristics and reported problematic shortages. Results Of 1422 women, 26.7% (n = 380) used mental health services in the last year, which most accessed through their HIV clinic. Thirty-eight percent (n = 541) reported that a shortage of mental health support was a problem in their care. Among this subset, 22.1% (n = 119) used services at their HIV clinic, 26.5% (n = 143) reported available services but did not use them, and 51.4% (n = 277) either indicated that these services were unavailable, did not know if such services were available, or were unengaged in HIV care. Factors associated with reporting problematic shortages included rural residence [adjusted odds ratio (aOR): 1.69, 95% confidence interval (CI): 1.03-2.77], higher education level (aOR: 1.43, 95% CI: 1.02-2.02), and higher HIV stigma score (aOR: 1.03, 95% CI: 1.02-1.03). Conversely, African/Caribbean/Black identity (aOR: 0.37, 95% CI: 0.26-0.54), history of recreational drug use (aOR: 0.56, 95% CI: 0.39-0.81), and Quebec residence (aOR: 0.69, 95% CI: 0.50-0.96) were associated with lower odds of reporting service shortages. Conclusion Our findings highlight the HIV clinic as the primary location of mental health service use. However, existing services may not be sufficient to reach all patients or meet specific needs. Furthermore, the low uptake among those reporting a shortage suggests a lack of connection to services or patient knowledge about their availability. Characteristics associated with reporting shortages reflect geographic and socioeconomic disparities that must be accounted for in future service design.